Uns i altres en la cartografia de la narrativa breu medieval - Ribera Llopis, Juan M. (Caplletra. Revista Internacional de Filologia, 2007)
Revision of a representative sample of short narrative in prose in order to detect, in the medieval cultural system, evidence of difference or diversity; likewise, the ways to portray the other one and to position literarily in front of it are revised. And all thatwithout considering if this other one was a Christian neighbour or a stranger, either in a cultural or spiritual way.